Indigenous African Synchronicity for Revitalizing Adult Education for Positive Social Change - Mejai Avoseh (Formare)
The need for and the importance of education, especially adult learning and education (ALE) continues to increase across the world especially given the challenges of our world, hyper-technology and Artificial Intelligence (AI). The purpose of this paper is the critical issue of the humanistic perspective of education. The central question is: “to what extent do the universal rendering and practice of ALE representative of the world?” And “how fitting is this universal frame within the indigenous contexts?”. This paper offers the Indigenous African synchronized and holistic lifelong learning as a viable compliment to revitalize education for positive social change.